2013
DOI: 10.1007/978-3-642-34359-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Linguistic Aspects of Geographic Space

Abstract: The first paper, entitled "Deficiencies of SQL as a GIS Query Language", argues that SQL and various extended versions of it are not adequate geographic query languages. They lack the integration of graphical display in retrieval and presentation of query results and do not support the set operations necessary for spatial query. In the second paper, "A Formalization of Metaphors and Image-Schemas in User Interfaces", an algebraic approach to formalization of interface metaphors is presented as a step toward th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(5 citation statements)
references
References 24 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Therefore, we often use a navigational aid to support the cognitive processes required to navigate as optimally as possible in an unknown environment (Ludwig, Müller, & Ohm, 2014). Several researchers have compared different kinds of navigation aids (e.g., Bakdash, Linkenauger, & Proffitt, 2008; Hirtle & Raubal, 2013; Ishikawa et al, 2008; Ishikawa & Takahashi, 2013; Klippel et al, 2010; Parush et al, 2007; Richter, Dara-Abrams, & Raubal, 2010; Willis et al, 2009). All found that modern digital navigation systems have a negative impact on the formation of mental spatial representations, but people using navigation systems are more time-efficient and effective in finding the route than people using paper maps (Dickmann, 2012; Lee & Cheng, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we often use a navigational aid to support the cognitive processes required to navigate as optimally as possible in an unknown environment (Ludwig, Müller, & Ohm, 2014). Several researchers have compared different kinds of navigation aids (e.g., Bakdash, Linkenauger, & Proffitt, 2008; Hirtle & Raubal, 2013; Ishikawa et al, 2008; Ishikawa & Takahashi, 2013; Klippel et al, 2010; Parush et al, 2007; Richter, Dara-Abrams, & Raubal, 2010; Willis et al, 2009). All found that modern digital navigation systems have a negative impact on the formation of mental spatial representations, but people using navigation systems are more time-efficient and effective in finding the route than people using paper maps (Dickmann, 2012; Lee & Cheng, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When continuously relying on this kind of positional updates, we do not attend to the information the traversed environment provides, and thus we lose the respective skill (Parush et al, 2007). But if the navigation system fails, navigators have to rely on their acquired knowledge, which would be challenging because not mentally processing properties along a travelled route results in decreased spatial knowledge in the end (e.g., Hirtle & Raubal, 2013; Huang, Schmidt, & Gartner, 2012; Münzer et al, 2006; Parasuraman, 2000; Parush et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These applications consider only mobility limitations. Others, such as Landmark Ontology for Hiking [71], are intended for elderly people. In this case, the application aids them to walk less when hiking.…”
Section: Related Workmentioning
confidence: 99%
“…Available: https://www.accessmap.io. [1] Access2All [2] Ciudades Patrimonio [15] Cardonha et al [23] Mediate [55] OpenTripPlanner [63] Sarjakoski et al [71] Wheelmap [83] Wheelmate [84] The need for data in order to provide intelligent urban mobility Collection (crowdsourcing) BUSUP [14] CIVITAS [24] Ferris et al [33] Lau and Ismail [49] Swiftly [75] Zimmermanet al [85] Publication and harmonization Bischof et al [12] CKAN ¡Error! No se encuentra el origen de la referencia.…”
Section: Definition and Characterization Of Smart Citiesmentioning
confidence: 99%
“…Consequently, humans use and describe landmarks on a day-to-day basis when navigating in a city or building and when formulating route instructions. However, landmark identification remains difficult from a research or commercial point of view, for example, to incorporate these navigational aids in path algorithms (Richter, 2013). This is important as even landmark knowledge acquired through external representations has an impact on human spatial activities (Kettunen, Irvankoski, Krause, & Sarjakoski, 2013).…”
Section: Introductionmentioning
confidence: 99%